Dokumentation og datering af teglmurværk. Om iagttagelser og deres samspil i bygningsarkæologien - Holst, Jens Christian (Hikuin, 2011)
Brick masonry, its documentation and dating By Jens Christian Holst Brick masonry is a specific category of architectural tradition Northern Germany and the Scandinavian countries have in common. It demands specific performances of documentation, dating and interpretation. The article deals with those contributions, a building archaeologist her- or himself might perform, and those better done by an expert. It is a rough sketch only, written from an empirical point of view, illustrated by a few examples. Steps of precision and accuracy in graphic resembling of a brick wall are named, what is achieved by them or not, and to which extent the competence of external surveying techniques is needed. Photographic and written documentation are merely quoted, the necessity of stratigraphic analysis is emphasized resulting from feature mapping and to be recorded by age mapping. The age layer model used, scaled into epochs, phases and stages, needs to be harmonized with the results of an archaeologist or a conservator dealing with the same building. Scientific methods to gain absolute datings out of the building material are shortly discussed. The architectural archaeologist´s own contribution is recognized in compiling chronologies of single and comprehensive material features, of brickmakers` as well as masons` techniques, to narrow down a possible date by comparison. Evaluation of written sources, to which precise dating is the key performance, cannot be discussed here. In the end possibilities occur to visualize historical stages of the architectural development, based on stratigraphic mapping. Clearing up the many stages of a building´s history until it became the one we know is seen as the main future field for our profession – not to be solved without help from many a friend.